Ultraboosted Zt and $$γ t$$ γ t production at the HL-LHC and FCC-hh - J. A. Aguilar–Saavedra (European Physical Journal C: Particles and Fields, 2017)
Abstract Searches for anomalous Zt and $$γ t$$ γ t production provide an excellent probe of flavour-changing top interactions when the energies considered are very large. In this note we estimate the sensitivity to these interactions at the high-luminosity phase of the LHC and a future 100 TeV pp collider (FCC-hh). For the LHC, the expected limits on $$t → uZ / uγ $$ t → u Z / u γ branching ratios from Zt and $$γ t$$ γ t production will reach the $$10^{-5}$$ 10 - 5 level, one order of magnitude better than the existing projections for $$t → uZ$$ t → u Z from $$t {\bar{t}}$$ t t ¯ production. For the FCC-hh, the limits on $$t → uZ / uγ $$ t → u Z / u γ could reach an impressive sensitivity at the $$10^{-6}$$ 10 - 6 level, with limits on $$t → cZ / cγ $$ t → c Z / c γ at the $$10^{-5}$$ 10 - 5 level.